Individual and combined effects of ammonia-N and sulfide on the immune function and intestinal microbiota of Pacific white shrimp Litopenaeus vannamei. Issue 92 (September 2019) - Jiang, Li; Feng, Jianxiang; Ying, Rui; Yin, Fangmin; Pei, Surui; Lu, Jianguo; Cao, Yiting; Guo, Jianlin; Li, Zufu
Abstract: In this study, we explored the individual and combined effects of ammonia-N and sulfide stress (1 mg/L sulfide and 15 mg/L ammonia-N) on the oxidation resistance, immune response and intestinal health of Litopenaeus vannamei during 72 h exposure. The total antioxidant capacity (T-AOC), malonaldehyde (MDA) and nitric oxide (NO) content, superoxide dismutase (SOD) and catalase activity (CAT), the immune-relative gene ( caspase-3, hsp70 and IMD ) expression in hepatopancreas and intestine of L.vannamei and the intestinal microbiota were measured. The result showed that MDA and NO contents in hepatopancreas of L. vannamei in all treatment groups increased and remain were at high levels at the end of the stress exposure. The L. vannamei employ antioxidant defense system by increasing the activities of T-AOC, SOD and CAT enzymes in hepatopancereas and intestine to reduce oxidant damage. More severe damages with combined ammonia-N and sulfide stress to antioxidant systems were observed. The gene expression results also demonstrated that antioxidant capacity of L. vannamei was severely impaired and the apoptosis cell was initiated under the ammonia-N and sulfide stress. In addition, the environmental stress also reshaped the intestinal microbial community structure of L. vannamei that a number of original genera decreased, such as Cellvibrio, Vibrio and Rheinheimera ; some new genera increased or appeared, such as Photobacterium in all treatment groups, Arcobacter and Fusibacter in sulfide stress group. Therefore, the health of L. vannamei was severely impacted when exposed to the stress of ammonia nitrogen and sulfide and these two factors can have weak synergic effects. Highlights: The oxidation resistance of Litopenaeus vannamei in ammonia-N and sulfide exposure were investigated. The antioxidant capacity of L. vannamei was severely impaired and the apoptosis was initiated. The intestinal microbiota of the L. vannamei were reshaped after 72 h exposure. The ammonia-N and sulfide have a weak synergic effects.